Coordination Polymers of Some Uranyl Salts Involving 4,4’ -Bipyrideyl, 4,4’ -Bipyridyl N,N’ -dioxide, 1,3-Bis(4-pyridyl) propane and Hexamethylenetetramine - S. Ahuja, I.; L. Yadava, C.; Tripathi, Shailendra (Asian Journal of Chemistry, 2010)
Analytical data and infrared spectral measurements down to 200 cm–1 on the coordination compounds formed by the interaction of uranyl chloride, thiocyanate, nitrate, sulphate and acetate with 4,4´-bipyridyl, 4,4´-bipyridyl N,N´-dioxide, 1,3-bis (4-pyridyl) propane and hexamethylenetetramine indicate that the complexes are coordination polymers having four or six coordination around the uranyl UO22+ ion with bidentate bridging organic ligand molecules and terminally bonded chloro and thiocyanato groups and bidentate chelating nitrato, sulphato and acetato groups in the solid state.